Three new species of Laccaria (Agaricales, Basidiomycota) from Southwest China (Yunnan) based on morphological and multi-gene sequence data - Li, Jing; Che, Nian-Jie; Cui, Yang-Yang (Frontiers in Microbiology, 2024)
The genus Laccaria has been reported from temperate and tropical areas and is an important constituent in forest ecosystems. However, the species diversity of Laccaria in Southwest China (Yunnan) has been underestimated. In this paper, descriptions based on morphological and multi-gene sequence data from internal transcribed spacer (ITS) region, large subunit ribosomal RNA gene (nrLSU), translation elongation factor 1-α (TEF1α) and the polymerase Ⅱ second largest subunit (RPB2) of three new Laccaria species from Southwest China (Yunnan) are reported. Two of these were characterized by orange pileus and globose to subglobose basidiospores: L. cinnabarina and L. spinulosa. While The first species L. cinnabarina has orange red colored basidiocarps with conspicuously pellucid-striate pattern, is characterized by its dark brown pileus often obviously depressed at center, globose to subglobose basidiospores, and a fibrillose stipe with longitudinally striations,. L. spinulosa has a brownish orange to brown fruiting body with light white pruinae and 2-spored basidia. Laccaria longistriata is characterized by brown to flesh-colored basidioma, prominently striate to sulcate pileus and echinate, globose to subglobose basidiospores. Laccaria spinulosa has a brownish orange to brown fruiting body with light white pruinae and 2-spored basidia. The three new species wereis described, illustrated and compared with closely related and similar species in morphology and phylogeny.